Analysis of colony development of Trigona sp. in Kawasan Rumah Pangan Lestari (KRPL) Central Lombok - Izza Melati Sukma; Syamsul Bahri; Karnan Karnan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
The Kawasan Rumah Pangan Lestari (KRPL) or Sustainable Food House Area integrated with Trigona sp. bee cultivation can be an alternative livelihood to improve the community's economy. This study aims at analyzing the development of bee colonies in KRPL in terms of the number of pollen pots and honey pots produced. The type of this research is descriptive qualitative. The study was conducted from October to November 2020. The samples used were 14 colonies, categorized as strong colonies, medium colonies and weak colonies. The increase in the number of empty pots, honey pots and pollen pots were observed every three days. Environmental factors such as temperature, humidity and light intensity, and the activity of the Trigona bees were also observed. The results showed that the average temperature at KRPL was 29.80 ÃÂ°C, with an average humidity of 69.62% and a light intensity of 22610 lux. Most of the increase in the highest total number of pots occurred in strong colonies. The number of empty pots, honey pots and pollen pots increased on different days. In the last week of the observation, most of the colonies did not increase in the number of pots. Development of Trigona sp. bee colonies in KRPL is considered slow even though the environmental conditions there are normal. Cultivation of Trigona sp. in KRPL should use strong colonies rather than medium and weak colonies.